2019
DOI: 10.20944/preprints201908.0050.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravitational Waves in Newton’s Gravitation and Criticism of Gravitational Waves Resulting from the General Theory of Relativity (LIGO)

Abstract: The most important conclusion from this article is that from the General Theory of Relativity (GTR) do not result any gravitational waves, but just ordinary modulation of the gravitational field intensities caused by rotating of bodies. If the LIGO team has measured anything, it is only this modulation, rather than the gravitational wave understood as the carrier of gravity. This discussion shows that using too complicated mathematics in physics leads to erroneous interpretation of results (in this case, perha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The problem that mathematical formulas can be assigned different physical interpretations is not just about the Lorentz transformation. For example, in the article [13], it was shown that gravitational waves should be interpreted as an ordinary modulation of gravitational field intensities.…”
Section: Discussionmentioning
confidence: 99%
“…The problem that mathematical formulas can be assigned different physical interpretations is not just about the Lorentz transformation. For example, in the article [13], it was shown that gravitational waves should be interpreted as an ordinary modulation of gravitational field intensities.…”
Section: Discussionmentioning
confidence: 99%